Diffusion lung imaging with hyperpolarized gas MRI. (16th December 2015) - Yablonskiy, Dmitriy A.; Sukstanskii, Alexander L.; Quirk, James D.
Abstract : Lung imaging using conventional 1 H MRI presents great challenges because of the low density of lung tissue, lung motion and very fast lung tissue transverse relaxation (typical T 2 * is about 1–2 ms). MRI with hyperpolarized gases ( 3 He and 129 Xe) provides a valuable alternative because of the very strong signal originating from inhaled gas residing in the lung airspaces and relatively slow gas T 2 * relaxation (typical T 2 * is about 20–30 ms). However, in vivo human experiments should be performed very rapidly – usually during a single breath‐hold. In this review, we describe the recent developments in diffusion lung MRI with hyperpolarized gases. We show that a combination of the results of modeling of gas diffusion in lung airspaces and diffusion measurements with variable diffusion‐sensitizing gradients allows the extraction of quantitative information on the lung microstructure at the alveolar level. From an MRI scan of less than 15 s, this approach, called in vivo lung morphometry, allows the provision of quantitative values and spatial distributions of the same physiological parameters as measured by means of 'standard' invasive stereology (mean linear intercept, surface‐to‐volume ratio, density of alveoli, etc.). In addition, the approach makes it possible to evaluate some advanced Weibel parameters characterizing lung microstructure: average radii of alveolar sacs and ducts, as well as the depth of their alveolar sleeves. Such measurements, providing in vivo information on the integrity of pulmonary acinar airways and their changes in different diseases, are of great importance and interest to a broad range of physiologists and clinicians. We also discuss a new type of experiment based on the in vivo lung morphometry technique combined with quantitative computed tomography measurements, as well as with gradient echo MRI measurements of hyperpolarized gas transverse relaxation in the lung airspaces. Such experiments provide additional information on the blood vessel volume fraction, specific gas volume and length of the acinar airways, and allow the evaluation of lung parenchymal and non‐parenchymal tissue. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Diffusion MRI with hyperpolarized gases provides quantitative information on lung microstructure at the alveolar level and makes it possible to measure the same morphometric parameters (mean linear intercept, surface‐to‐volume ratio, number of alveoli per unit volume) as have been traditionally obtained by means of invasive stereology.